THE CONTINUITY OF AMRUS NATALSYA’S POPULIST PARADIGM, ICONOGRAPHY-ICONOLOGY REVIEW OF “TANAH AIRKU” (2013) PAINTING - Miftahul Khairi (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2019)
This study analyzes the Amrus Natalsya’s painting entitled "Tanah Airku" (2013). As a senior Indonesian painter with the ideology of "kiri" that’s popular in the history of Indonesia modern art certainly has strongly experiences about social phenomena that occur in Indonesia. By analyzing this painting, the author wants to see the continuity in expressing social phenomena including style, theme, concept, and meaning of his work. Research problem was revealed through the approach of art history and a grand theory of iconography and iconology from Panofsky. The research result is a style of painting categorized in expressionism style with metaphorical symbols. This style is developed in the era of art pluralism. The theme of this painting is the power of people in defending their rights with the basic concepts of resistance and struggle. These themes are variants of the theme and concept of the aesthetic paradigm from social realism convention during LEKRA. Symbolic value expressed by Amrus Natalsya in the painting "My Fatherland" (2013) is the crystallization of human’s struggle as the living symbol of defending their rights. Based on such analysis, it’s shown the continuity of expression of revolutionary populist paradigm in his paintings with new forms and expressions along with the spirit of the era.